Knowledge on Toothbrush Contamination and Disinfection Practice among Students of a Dental Institution in Nepal - Dahal, Srijana; Poudel, Prakash; Adhikari, Shradha; Acharya, Pratikshya; Dhakal, Samikshya; Giri, Simran (Journal of Nepalese Society of Periodontology and Oral Implantology, 2019)
Introduction: Toothbrush is the most common oral hygiene aid used by millions of people all around the world. Toothbrushes can either be discarded at an interval of three months or can be disinfected by different methods. Objective: This study was conducted to assess the knowledge on toothbrush contamination and practice of disinfection among dental students and interns of a dental institution of Kathmandu, Nepal. Methods: A descriptive cross-sectional study was conducted among 212 undergraduate dental students and interns of Kathmandu Medical College, Duwakot, Nepal using a self-administered questionnaire. Mean, standard deviation, percentage were calculated for descriptive statistics. Results: Mean age of the study participants was 21.28±1.897 years. Most of the interns 18 (69.2%) had some knowledge regarding toothbrush cleaning and disinfection. Majority of the participants 186 (87.73%) reported bacteria as most susceptible microorganisms causing toothbrush contamination and sharing the toothbrush as common mode of transmission of infection. Most of them, 147 (69.34%) did not have any idea about toothbrush disinfection methods for general population. However, they felt it necessary in special needs patients. Conclusion: This study concluded that there is variable knowledge regarding toothbrush contamination and disinfection practice among undergraduate dental students and interns due the difference in their academic level and experience in the clinical work